The Arthritis Therapy of Temporomandibular Joint - V. Machoň; J. Paska (Czech Dental Chamber, 2007)
This article is about therapy of the arthritis of the TMJ (comparisson between non-surgery therapy and miniinvasive therapy and combination - arthrocenthesis with occlusal splint together). The most effective method of the therapy of the arthritis is combination arthrocenthesis with occlusal splint (87,5% good results 3 months after beginning of the therapy) - in comparisson with other methods (analgotherapy 53%, occlusal splint 75%, arthrocenthesis 84%).